Acid influences postharvest quality and oxidative activity of gerbera cut flowers - de Lima Silva, Yasmin P.; da Rosa Ferraz Jardim, Alexandre M.; da Silva, Luzia F.; de Medeiros, Damiana C.; da Costa, Franciscleudo B.; de Souza, Angela V. [UNESP]; Cerqueira, Reginaldo C.; da Silva, Rainério M.; da Vieira, Marcos R.S. (Society for the Advancement of Horticulture, 2020)
Gerbera is a very popular ornamental plant and used in gardens as well as for cut flower. However, as a cut flower its postharvest quality is minimal, efforts are required to increase longivity and one of the possible way is to use acidic solutions. The study was conducted ot understand if the action of maintenance solutions with acids influence the postharvest physiology of gerbera cv. ‘Piang’. The experimental design was factorial completely randomized consisting of two factors: four postharvest treatments and seven evaluation times. The flowers were kept in 200 mg L-1 of citric acid solution (ACS reagent, ≥ 99.5 % - Sigma-Aldrich), 200 mg L-1 of boric acid solution (ACS reagent, ≥ 99.5 %) and 200 mg L-1 of salicylic acid solution (ACS reagent, ≥ 99.0 %) and potable water as a control. During the postharvest period, fresh mass loss, water absorption, petal luminosity, total longevity, peroxidase (POD) enzyme activity, superoxide dismutase (SOD), total protein and total carbohydrate content were studied. Treatments with boric and salicylic acids recorded higher percentage of fresh weight loss. Citric acid showed higher water absorption rate and better appearance indicated by luminosity of the petals. The total protein and carbohydrate content decreased during the evaluation period but in the citric acid treatment, the reduction was not so significant. On the other hand, citric acid induced higher peroxidase and superoxide dismutase activity on the second day of evaluation and lower activity until the tenth day.
Keywords: ethylene; Gerbera jamesonii Bolus; oxygen reactive species; senescence